2018
DOI: 10.1021/acs.nanolett.7b04818
|View full text |Cite
|
Sign up to set email alerts
|

Highly Localized Charge Transfer Excitons in Metal Oxide Semiconductors

Abstract: The ability to observe charge localization in photocatalytic materials on the ultrafast time scale promises to reveal important correlations between excited state electronic structure and photochemical energy conversion. Of particular interest is the ability to determine hole localization in the hybridized valence band of transition metal oxide semiconductors. Using femtosecond extreme ultraviolet reflection absorption (XUV-RA) spectroscopy we directly observe the formation of photoexcited electrons and holes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
104
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(116 citation statements)
references
References 41 publications
9
104
3
Order By: Relevance
“…The characteristic time constants extracted for the differently doped films are listed in Table 1 and the fits are shown in Figure S3 (Supporting Information). The shorter decay time is between 20 and 50 ns for all of the dopants, which is two to three orders of magnitude larger than what is commonly accepted for the life time of minority charge carriers in hematite . This long lifetime could explain recent results, which have shown that a small percentage of holes can be extracted from depths of ≈700 nm in hematite .…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The characteristic time constants extracted for the differently doped films are listed in Table 1 and the fits are shown in Figure S3 (Supporting Information). The shorter decay time is between 20 and 50 ns for all of the dopants, which is two to three orders of magnitude larger than what is commonly accepted for the life time of minority charge carriers in hematite . This long lifetime could explain recent results, which have shown that a small percentage of holes can be extracted from depths of ≈700 nm in hematite .…”
Section: Resultsmentioning
confidence: 72%
“…Hematite charge carrier dynamics have been studied extensively by transient absorption spectroscopy (TAS), 4D electron energy loss spectroscopy, and extreme ultra‐violet (XUV) spectroscopy . These different studies have shown relaxation dynamics in hematite spanning a wide range of timescales, with no consensus on the attribution of extracted time constants to specific processes such as charge carrier recombination, trapping, polaronic state formation, lattice expansion and cooling, or long lived holes on the surface …”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the above mentioned routes induced defects may lead to anistropically scattered photons due to the unexpected lattice distortion and therefore result in dramatically increased electron/hole pair recombination rate. [ 15 ] Alternatively, constructing Schottky catalyst by coupling semiconductor with uniquely designed metal terminals, the so‐called Janus‐structure, is receiving growing attention due to its outstanding characteristics, such as passivation effect on the surface defects of semiconductors, enhanced light harvesting due to surface plasmon effect, efficient charge separation and transfer efficiency at the interface between different components, and therefore enhanced photocatalytic reaction kinetics. [ 16 ] In this regard, constructing ingenious Janus‐structured Ti 3 C 2 MQD Schottky‐photocatalyst to realize high performance PEC water oxidation with excellent optical‐response, carrier separation and transport efficiency is of fundamental importance and great challenge.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the ground state x-ray absorption spectrum and any photoexcited changes seldom match the expected effects from visible and infrared measurements of the same material [24][25][26] . In the case of localized valence orbitals, such as in the 3d transition metals, the core-hole interaction is strong enough that only the photoexcited change in elemental oxidation state can be measured [27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%